Theoretical and experimental studies on the motion and thermal states of oil droplet in a bearing chamber. (December 2016) - Sun, Hengchao; Chen, Guoding; Zhang, Yonghong; Wang, Li'na
Study on the motion and thermal states of oil droplet is an important part of research on the oil/air two-phase flow and heat transfer in an aero engine bearing chamber. In this paper, dimensional analysis is applied to the airflow analysis of bearing chamber. That makes the analysis model suitable for a wide range of geometric and operating conditions. Moreover, the temperature solution is added to the oil droplet motion analysis. That could promote the calculation accuracy of the droplet trajectory, velocity, and temperature. Firstly, the similarity criteria of the airflow in a bearing chamber are determined based on the dimensional analysis. The airflow distribution general formulas are proposed based on the numerical results of airflow velocity and temperature. The general formulas include 14 similarity criteria and are suitable for various geometric and operating conditions. The reliability of the general formulas is verified by some available experimental results. Secondly, the difference equations of the oil droplet velocity and temperature are listed by the difference method. The velocity and temperature of the droplet are obtained using a step-by-step method. The influence of droplet diameter, shaft rotational speed, air flow rate, and temperature on the oil droplet trajectory, velocity, and temperature are discussed. Thirdly, a test facility is built in order to investigate into the oil droplet motion and thermal states in a bearing chamber. The trajectory and velocity of the oil droplet are measured by the high-speed photography. Lastly, the proposed theoretical method about the oil droplet motion and thermal states is verified by above measurement results. The work in this paper may have a certain significance for perfecting the research system and improving the research level on the oil/air two-phase flow and heat transfer in an aero engine bearing chamber.